Long-acting reversible contraception immediately after medical abortion: systematic review with meta-analyses. (25th February 2020) - Schmidt-Hansen, Mia; Hawkins, James E; Lord, Jonathan; Williams, Kelly; Lohr, Patricia A; Hasler, Elise; Cameron, Sharon
Abstract: BACKGROUND: Long-acting reversible contraceptives (LARCs) are safe, effective and convenient post-abortal methods. However, there is concern that some LARCs may reduce the effectiveness of abortifacient drugs or result in other adverse outcomes. OBJECTIVE AND RATIONALE: We undertook two systematic reviews to examine the early administration of LARCs in women undergoing medical abortion with mifepristone and misoprostol. (i) For women who are having a medical abortion and who plan to use a progestogen-only contraceptive implant or injectable, does administration of the contraception at the same time as mifepristone influence the efficacy of the abortion? (Implant/injectable review). (ii) For women who have had a medical abortion, how soon after expulsion of the products of conception is it safe to insert an intrauterine contraceptive device/system? (LNG-IUS/Cu-IUD review). SEARCH METHODS: On 19 November 2018, we searched Embase Classic, Embase; Ovid MEDLINE(R) including Daily and Epub Ahead-of-Print, In-Process and Other Non-Indexed Citations; the Cochrane Library; Cinahl Plus; and Web of Science Core Collection. Eligible studies were randomised controlled trials (RCTs), in English from 1985 (Implant/injectable review) or 2007 (LNG-IUS/Cu-IUD review) onwards, conducted in women undergoing medical abortion with mifepristone and misoprostol and studying either (i) simultaneous administration of mifepristone and a progestogen-only contraceptive implant or injectable compared to administration >24 h after mifepristone, or (ii) immediate insertion of intrauterine contraception after expulsion of the products of conception compared to early insertion (≤7 days) or to delayed insertion (>7 days) or early compared to delayed insertion. One author assessed the risk of bias in the studies using the Cochrane Collaboration checklist for RCTs. All the outcomes were analysed as risk ratios and meta-analysed in Review Manager 5.3 using the Mantel–Haenszel statistical method and a fixed-effect model. The overall quality of the evidence was assessed using GRADE. OUTCOMES: Two RCTs ( n = 1027) showed lower 'subsequent unintended pregnancy' rates and higher 'patient satisfaction' rates, and no other differences, after simultaneous administration of mifepristone and the implant compared to delayed administration. One RCT ( n = 461) showed higher 'patient satisfaction' rates after simultaneous administration than after delayed administration of mifepristone and the injectable, but no other differences between these interventions. Three RCTs ( n = 536) found no differences other than higher copper IUC uptake after early compared to delayed insertion at ≤9 weeks of gestation and higher rates of IUC expulsion, continuation and uptake after immediate compared to delayed insertion at 9 +1 –12 +0 weeks of gestation and higher IUC continuation rates after immediate compared to delayed insertion at 12 +1 –20 +0 weeks of gestation. The quality of this evidence ranged from very low to high and was mainly compromised by low event rates, high attrition and no blinding. WIDER IMPLICATIONS: The contraceptive implant or injectable should be offered on the day of taking mifepristone. Intrauterine methods of contraception should be offered as soon as possible after expulsion of the pregnancy.